Preparation method of nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current

Nanodiamond/graphite composite thin film electrodes were prepared through hot wire chemical vapor deposition and electrochemical anodization treatment, which solved the problems of high background current and hydrogen evolution side reaction in electrochemical reduction reaction, and achieved electrode materials with high hydrogen evolution potential and low background current. Suitable for electrochemical reduction reactions and battery energy storage fields.

CN119243207APending Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411350225.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

There are competitive side reactions of high background current and proton direct reduction to hydrogen in existing electrochemical reduction reactions, which reduces the yield and signal-to-noise ratio of carbon dioxide reduction and nitrogen reduction reactions, and the hydrogen evolution potential and background current of traditional electrode materials are difficult to achieve. Meet industrial application needs.

Method used

Nanodiamond/graphite composite thin film electrodes were prepared by hot wire chemical vapor deposition, and electrochemical anodization treatment was carried out to increase their hydrogen evolution potential and reduce the background current, achieving high hydrogen evolution potential and low background current electrode materials.

Benefits of technology

The hydrogen evolution potential of nanodiamond/graphite composite thin film electrodes was significantly improved to -2.10V (vs RHE), and the background current dropped to 0.73mA/cm2, which was much higher than that of traditional electrode materials and commercial electrodes, and had wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005062149880000011
    Figure HDA0005062149880000011
  • Figure HDA0005062149880000012
    Figure HDA0005062149880000012
  • Figure HDA0005062149880000013
    Figure HDA0005062149880000013
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current, which comprises the following steps: firstly, preparing the nano-diamond / graphite composite film electrode through hot filament chemical vapor deposition, and then carrying out electrochemical anodic oxidation treatment on the composite film electrode. And finally obtaining the nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current. According to the method disclosed by the invention, the content of diamond in the composite film electrode can be increased, and the oxygen element is grafted on the surface of the nano-diamond / graphite composite film electrode, so that the background current of the nano-diamond / graphite composite film electrode is reduced while the hydrogen evolution potential of the nano-diamond / graphite composite film electrode is improved; and a new thought and scheme are provided for design and preparation of the novel nano-diamond film-based composite electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nano diamond / graphite composite film electrode with high hydrogen evolution potential and low background current. Background Art

[0002] Electrochemical reduction reactions such as carbon dioxide reduction and nitrogen reduction are one of the important technical approaches to achieve carbon neutrality and carbon peak goals. However, in the process of these electrochemical reduction reactions, competitive side reactions of direct reduction of protons to hydrogen often occur, which will reduce the total yield of the target product of the reduction reaction. The theoretical potential for hydrogen evolution in the electrolysis of aqueous solution is 0V (vsRHE), so the key to inhibiting the hydrogen evolution side reaction is to prepare cathode materials with high hydrogen evolution overpotential. Traditional high hydrogen evolution potential electrode materials include bismuth, tin, zinc and glassy carbon, and their hydrogen evolution potentials for electrolysis of water are approximately -0.36V (vs RHE), -0.81V (vsRHE), -1.20V (vs RHE), and -1.1~1.2V (vs RHE), respectively. The hydrogen evolution potential of commercial boron-doped diamond thin film electrodes is slightly higher than that of traditional electrode materials, about -1.2~-1.5V (vs RHE). In industrial applications, the hydrogen evolution potential still needs to be further improved to effectively inhibit the occurrence of hydrogen evolution side reactions during electrochemical reduction reactions.

[0003] In addition, high background current will also have a negative impact on electrochemical reactions such as carbon dioxide reduction and nitrogen reduction. For example, high background current will reduce the signal-to-noise ratio of the electrochemical reduction reaction, thereby masking the current signal of the target reduction reaction, making it difficult to distinguish the current signal of the target reduction reaction from the background noise. High background current may have similar characteristics to the current signal of the target reduction reaction, resulting in the generation of false positive signals, misleading researchers to believe that the product of the target reduction reaction has been produced. The background current of the widely used low background current glassy carbon electrode in 1M KCl solution is 69.87mA / cm 2 The background current of the boron-doped diamond film electrode in the same solution was further reduced to 22.97 mA / cm 2 In practical applications, it is still necessary to further reduce the background current to reduce its negative impact on the electrochemical reduction reaction. However, there are few studies focusing on the hydrogen evolution potential of diamond electrodes.

[0004] In the previous study, our research group conducted thermal oxidation treatment on the prepared nanodiamond / graphite composite film electrode, increasing its hydrogen evolution potential from -1.44V (vs RHE) to -1.81V (vs RHE), and the background current from 35.71mA / cm 2 Down to 16.39mA / cm 2. However, it is difficult to accurately control the degree of oxidation of the nanodiamond / graphite composite thin film electrode by thermal oxidation treatment, resulting in poor repeatability of the treatment results; at the same time, the thermal stress caused by thermal oxidation will lead to stress accumulation inside the composite thin film electrode material, thereby affecting the service life of the composite thin film electrode material. The present invention proposes to subject the prepared nanodiamond / graphite composite thin film electrode to an electrochemical anodization treatment which can accurately control the degree of oxidation, has high repeatability of the results and relatively mild treatment conditions. This method increases the hydrogen evolution potential of the nanodiamond / graphite composite thin film electrode while reducing its background current, and increases the electrode hydrogen evolution potential to -2.10V (vs RHE), which is much higher than traditional cathode materials with high hydrogen evolution potentials such as bismuth, tin, and zinc, and commercial boron-doped diamond thin film electrodes; the background current is as low as 0.73mA / cm 2 , which is much lower than that of glassy carbon electrode, boron-doped diamond film electrode and nano-diamond / graphite composite film electrode after thermal oxidation treatment. Summary of the invention

[0005] The purpose of the present invention is to prepare a nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current. Firstly, the nano-diamond / graphite composite thin film electrode is prepared by hot wire chemical vapor deposition, and then the composite thin film electrode is subjected to electrochemical anodization treatment to finally obtain a nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current comprises the following steps:

[0008] (1) Seed crystal pretreatment

[0009] Ultrasonic dispersion of diamond powder in deionized water to obtain diamond seeding liquid, taking the diamond seeding liquid on a polishing flannel, grinding a single crystal silicon wafer back and forth at the seeding liquid to grind the seeding crystal, then placing the single crystal silicon wafer after the seeding crystal is ground in the diamond seeding liquid for ultrasonic seeding, then taking it out, washing it with deionized water, and drying it with nitrogen to obtain a single crystal silicon wafer after seeding;

[0010] The particle size of the diamond powder is preferably 500 nm;

[0011] The preferred mass volume ratio of diamond powder to deionized water is 1:100, g / mL;

[0012] Preferably, the diamond powder is ultrasonically dispersed in deionized water for 20 min;

[0013] The preferred grinding time for the seed crystal is 20 min;

[0014] The preferred ultrasonic seeding time is 30 min;

[0015] (2) Hot Wire Chemical Vapor Deposition

[0016] Using the seeded single crystal silicon wafer obtained in step (1) as a substrate, tantalum wire as a metal wire, and acetone as a carbon source, a nano-diamond / graphite composite thin film electrode is prepared by hot wire chemical vapor deposition;

[0017] The specific operation method is as follows: a seeded single crystal silicon wafer is placed as a substrate into a hot wire chemical vapor deposition device, a tantalum wire is used as a metal wire, and acetone is used as a carbon source. A high-purity hydrogen gas with a flow rate of 80 sccm is used to bubble the acetone into the reaction chamber, and a high-purity hydrogen gas with a flow rate of 200 sccm is introduced at the same time. The growth power is controlled to be 2200 W, the growth pressure is 1.0 kPa, and the growth time is 90 min. After the growth is completed, the acetone is stopped, and the voltage is slowly reduced to 0 V at a rate of 1 V / min in high-purity hydrogen, so that the power is reduced to 0 W, and a nano-diamond / graphite composite thin film electrode is obtained;

[0018] (3) Electrochemical anodizing treatment

[0019] The nano-diamond / graphite composite film electrode obtained in step (2) is placed in a H2SO4 solution and subjected to electrochemical anodization treatment at a voltage of +0.5V for 30 to 90 minutes to obtain the nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current;

[0020] The preferred concentration of H2SO4 solution is 0.5M;

[0021] Electrochemical anodizing treatment can be performed using an electrochemical workstation.

[0022] The method of the present invention can increase the diamond content in the composite thin film electrode and graft oxygen elements onto the surface of the nano-diamond / graphite composite thin film electrode, thereby increasing the hydrogen evolution potential of the nano-diamond / graphite composite thin film electrode while reducing its background current, providing a new idea and solution for the design and preparation of a novel nano-diamond film-based composite electrode.

[0023] The beneficial effects of the present invention are mainly reflected in:

[0024] 1. The electrochemical workstation is used to perform anodization on the composite thin film electrode. The operation is convenient and simple. By changing the time of anodization, the degree of oxidation of the film can be accurately controlled. The repeatability is high and the hydrogen evolution potential of the composite thin film electrode can be effectively improved.

[0025] 2. The composite film electrode has an extremely high hydrogen evolution potential, which can reach up to -2.10V (vsRHE), which is much higher than electrode materials with high hydrogen evolution potential such as bismuth, tin, zinc, and boron-doped diamond film electrodes;

[0026] 3. The composite film electrode has an extremely low background current, the lowest background current can reach 0.73mA / cm 2 , which is an electrode material with low background current, far lower than that of glassy carbon electrodes, boron-doped diamond film electrodes, nanodiamond / graphite composite film electrodes after thermal oxidation treatment, etc. It has great application prospects in the fields of electrochemical reduction reactions, battery energy storage and electrochemical analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1 at a magnification of 10,000.

[0028] Figure 2 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1 at a magnification of 100,000.

[0029] Figure 3 The nano-diamond / graphite composite film electrode NCD-G-30 treated at a voltage of +0.5 V for 30 min was electrochemically oxidized at 800-2200 cm -1 Raman spectrum of .

[0030] Figure 4 The nano-diamond / graphite composite film electrode NCD-G-30 treated with a voltage of +0.5 V and electrochemically oxidized for 30 min in Example 1 has a peak value of 2200-3500 cm -1 Raman spectrum of .

[0031] Figure 5 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1 in 1M KCl electrolyte at a scan rate of 100 mV / s.

[0032] Figure 6 Cyclic voltammogram of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1 in an electrolyte of 1M KCl+1mM K3Fe(CN)6 at a scan rate of 100mV / s.

[0033] Figure 7 Broad spectrum of the XPS energy spectrum of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1.

[0034] Figure 8 Fitting diagram of O1s spectrum in XPS spectrum of nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in Example 1.

[0035] Fig. 9 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2 at a magnification of 10,000.

[0036] Fig.10 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2 at a magnification of 100,000.

[0037] Fig.11 In Example 2, the nano-diamond / graphite composite film electrode NCD-G-60 was electrochemically oxidized for 60 min at a treatment voltage of +0.5 V at 800-2200 cm -1 Raman spectrum of .

[0038] Fig.12 In Example 2, the nano-diamond / graphite composite film electrode NCD-G-60 was electrochemically oxidized for 60 min at a treatment voltage of +0.5 V at 2200-3500 cm -1 Raman spectrum of .

[0039] Fig.13 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2 in 1M KCl electrolyte at a scan rate of 100 mV / s.

[0040] Fig.14 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2 in 1M KCl+1mM K3Fe(CN)6 electrolyte at a scan rate of 100mV / s.

[0041] Fig.15 Broad spectrum of the XPS energy spectrum of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2.

[0042] Fig.16Fitting diagram of O1s spectrum in XPS spectrum of nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in Example 2.

[0043] Fig.17 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3 at a magnification of 10,000.

[0044] Fig.18 FESEM image of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3 at a magnification of 100,000.

[0045] Fig.19 In Example 3, the nano-diamond / graphite composite film electrode NCD-G-90, which was electrochemically oxidized for 90 min at a treatment voltage of +0.5 V, had a peak value of 800-2200 cm -1 Raman spectrum of .

[0046] Fig. 20 In Example 3, the nano-diamond / graphite composite film electrode NCD-G-90, which was electrochemically oxidized for 90 min at a treatment voltage of +0.5 V, had a peak value of 2200-3500 cm -1 Raman spectrum of .

[0047] Fig.21 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3 in 1M KCl electrolyte at a scan rate of 100 mV / s.

[0048] Fig. 22 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3 in 1M KCl+1mM K3Fe(CN)6 electrolyte at a scan rate of 100mV / s.

[0049] Fig.23 Broad spectrum of the XPS energy spectrum of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3.

[0050] Fig.24 Fitting diagram of O1s spectrum in XPS spectrum of nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V in Example 3.

[0051] Fig.25 FESEM image of the nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 at 10,000 times magnification.

[0052] Fig.26 FESEM image of the nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 at 100,000 times magnification.

[0053] Fig. 27 The nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 has a wavelength of 800-2200 cm -1 Raman spectrum of .

[0054] Fig.28 The nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 has a wavelength of 2200-3500 cm -1 Raman spectrum of .

[0055] Fig.29 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 in 1M KCl electrolyte at a scan rate of 100 mV / s.

[0056] Fig.30 Cyclic voltammetry curve of the nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1 in 1M KCl+1mM K3Fe(CN)6 electrolyte at a scan rate of 100mV / s.

[0057] Fig.31 Broad spectrum of the XPS energy spectrum of the nano-diamond / graphite composite thin film electrode NCD-G in Comparative Example 1.

[0058] Fig.32 Fitting diagram of O1s spectrum in XPS spectrum of nano-diamond / graphite composite film electrode NCD-G in Comparative Example 1.

[0059] Fig.33 Cyclic voltammetry curve of the commercial glassy carbon electrode purchased in Comparative Example 2 in 1M KCl electrolyte at a scan rate of 100 mV / s.

[0060] Fig.34 Cyclic voltammetry curve of the commercial boron-doped diamond film electrode purchased in Comparative Example 3 in 1M KCl electrolyte at a scan rate of 100 mV / s. DETAILED DESCRIPTION

[0061] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0062] Example 1

[0063] Diamond powder with a particle size of 500nm and deionized water are mixed evenly in a ratio of 1g:100ml, and the mixed solution is then placed in an ultrasonic cleaner for 20 minutes to evenly disperse the diamond powder in the solution to obtain a diamond seeding solution; the diamond seeding solution is taken on a polishing flannel cloth, and a single crystal silicon wafer is ground back and forth at the seeding solution for 20 minutes to grind the seeding crystal, and then the ground seeded single crystal silicon wafer is placed in the diamond seeding solution for 30 minutes of ultrasonic seeding, and then the obtained single crystal silicon wafer is washed with deionized water and blown dry with nitrogen to finally obtain a seeded single crystal silicon wafer.

[0064] The seeded single crystal silicon wafer was placed as a substrate in a hot wire chemical vapor deposition device, tantalum wire was used as the metal wire, acetone was used as the carbon source, and high-purity hydrogen with a flow rate of 80sccm was used to bring the acetone into the reaction chamber, and high-purity hydrogen with a flow rate of 200sccm was introduced, the growth power was controlled to be 2200W, the growth pressure was 1.0kPa, and the growth time was 90min; after the growth was completed, the acetone was stopped, and the voltage was slowly reduced to 0V at a rate of 1V / min in high-purity hydrogen, so that the power was reduced to 0W, and a nanodiamond / graphite composite thin film electrode was obtained, which was named NCD-G.

[0065] The processing voltage of the electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., CHI750E) was set to +0.5V, and the nanodiamond / graphite composite film electrode NCD-G was placed in a 0.5M H2SO4 solution and connected to the electrochemical workstation for 30 minutes of electrochemical anodization treatment to obtain a nanodiamond / graphite composite film electrode with high hydrogen evolution potential and low background current, which was named NCD-G-30.

[0066] The surface morphology of NCD-G-30 was observed by field emission scanning electron microscopy (FESEM); the phase components of NCD-G-30 were detected by microconfocal laser Raman spectrometer (Raman); the electrochemical related properties of NCD-G-30 were detected by electrochemical workstation; and the element content and functional group composition on the surface of NCD-G-30 were characterized by X-ray photoelectron spectrometer (XPS).

[0067] Figure 1 , Figure 2 The FESEM images of the nano-diamond / graphite composite film electrode NCD-G-30 at 10,000 times and 100,000 times magnification respectively, after electrochemical oxidation for 30 minutes at a treatment voltage of +0.5V. Figure 1 It can be seen that the NCD-G-30 composite thin film electrode is a dense film formed by connecting many large spherical particles, and the silicon substrate is not exposed; Figure 2It can be observed that there are many angular and irregularly shaped tiny nanoparticles on the surface of these large spherical particles.

[0068] Figure 3 , Figure 4 The nano-diamond / graphite composite film electrode NCD-G-30 was electrochemically oxidized for 30 min at a treatment voltage of +0.5 V at 800-2200 cm -1 and 2200-3500cm -1 Raman spectrum of the band. Figure 3 The Raman spectrum in the image is composed of 1140, 1250, 1332, 1350, 1470, 1580cm -1 The typical Raman spectrum of nanodiamond thin film electrode is composed of six characteristic peaks. -1 and 1470cm -1 The peak at is attributed to the sp 2 CC vibration, 1250cm -1 The peak at 1332 cm is caused by the broadened vibrational density of states of diamond clusters with smaller grain size and tetrahedral amorphous carbon. -1 The peak at 1350cm is a typical diamond characteristic peak. -1 The D peak at the graphite grain boundary is disordered or other structural defects at the sp 2 Bond stretching vibration related, 1580cm -1 The G peak at is caused by the sp 2 The hybrid CC bond vibration is generated. In addition, Figure 4 The Raman spectrum of the -1 There are two characteristic peaks, corresponding to the 2D peak of the double frequency Raman characteristics of the complete dispersion of phonons related to single-layer or few-layer graphene and the D+D' peak related to the expression of auxiliary defects. The content of diamond phase in the thin film electrode can be calculated, where C d and C i Raman spectrum 800-2200cm -1 The integrated area of ​​the diamond peak and non-diamond phase peak in the Raman spectrum; I D / I G The value is often used to indicate the degree of defects in the graphite phase in thin film electrodes. D / I G The larger the value, the greater the degree of defects in the graphite phase in the thin film electrode; the half-peak width of the G peak can reflect the distortion of the bond length and bond angle of graphite, and is often used to indicate the degree of order of graphite inside the thin film electrode. Generally, the smaller the half-peak width of the G peak, the higher the degree of order of graphite inside the thin film electrode. Figure 3 It can be calculated that the diamond content in NCD-G-30 is 28.41%. D / I G The value is 1.07, and the half-peak width of the G peak is 100.54 cm -1 .

[0069] Figure 5 , Figure 6 The cyclic voltammetry curves of the nano-diamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5 V in 1M KCl and 1M KCl+1mM K3Fe(CN)6 electrolytes at a scan rate of 100mV / s; Figure 5 It can be seen that the potential window of NCD-G-30 is 3.45V (vs RHE), the hydrogen evolution potential is -1.64V (vs RHE), and the background current is 4.59mA / cm 2 .Depend on Figure 6 It can be seen that the electrochemical active area C of NCD-G-30 A 461.7μC / cm 2 Compared with NCD-G in Comparative Example 1, the hydrogen evolution potential of NCD-G-30 in Example 1 shifted negatively by about 0.06 V, and the background current decreased by about 1.78 mA / cm 2 Compared with the glassy carbon electrode and boron-doped diamond film electrode purchased in Comparative Examples 2 and 3, the background current of NCD-G-30 is 65.28 mA / cm lower than that of the commercially purchased glassy carbon electrode and boron-doped diamond film electrode. 2 , 18.38mA / cm 2 .

[0070] Figure 7 , Figure 8 They are the XPS spectrum corresponding to the broad spectrum and the fitting diagram of the O1s spectrum of the nanodiamond / graphite composite film electrode NCD-G-30 electrochemically oxidized for 30 min at a treatment voltage of +0.5V. Figure 7 Semi-quantitative calculation of the relative contents of C 1s and O 1s in NCD-G-30 showed that the content of C1s was 89.83At%, and the content of O 1s was 7.17At%. Figure 8 As shown, the O 1s energy spectrum is mainly composed of three characteristic peaks with binding energies of 531.3eV, 532.2eV, and 533.1eV. The characteristic peak at 531.3eV is the peak related to the C=O bond, the characteristic peak at 532.2eV is the peak related to the C-OH bond, and the characteristic peak at 533.1eV is the peak related to the COC bond. Figure 8Semi-quantitative calculation of the relative content of oxygen-containing groups in the O1s spectrum shows that the content of C=O is 2.24At%, the content of C-OH is 2.52At%, and the content of C=O is 2.41At%. Compared with NCD-G in Comparative Example 1, the O1s content of NCD-G-30 in Example 1 increases by about 2.36At%.

[0071] Example 2

[0072] Diamond powder with a particle size of 500nm and deionized water are mixed evenly in a ratio of 1g:100ml, and the mixed solution is then placed in an ultrasonic cleaner for 20 minutes to evenly disperse the diamond powder in the solution to obtain a diamond seeding solution; the diamond seeding solution is taken on a polishing flannel cloth, and a single crystal silicon wafer is ground back and forth at the seeding solution for 20 minutes to grind the seeding crystal, and then the ground seeded single crystal silicon wafer is placed in the diamond seeding solution for 30 minutes of ultrasonic seeding, and then the obtained single crystal silicon wafer is washed with deionized water and blown dry with nitrogen to finally obtain a seeded single crystal silicon wafer.

[0073] The seeded single crystal silicon wafer was placed as a substrate in a hot wire chemical vapor deposition device, tantalum wire was used as the metal wire, acetone was used as the carbon source, and high-purity hydrogen with a flow rate of 80sccm was used to bring the acetone into the reaction chamber, and high-purity hydrogen with a flow rate of 200sccm was introduced, the growth power was controlled to be 2200W, the growth pressure was 1.0kPa, and the growth time was 90min; after the growth was completed, the acetone was stopped, and the voltage was slowly reduced to 0V at a rate of 1V / min in high-purity hydrogen, so that the power was reduced to 0W, and a nanodiamond / graphite composite thin film electrode was obtained, which was named NCD-G.

[0074] The processing voltage of the electrochemical workstation was set to +0.5V, and the nanodiamond / graphite composite film electrode NCD-G was placed in a 0.5M H2SO4 solution and connected to the electrochemical workstation for 60 minutes of electrochemical anodization treatment to obtain a nanodiamond / graphite composite film electrode with high hydrogen evolution potential and low background current, which was named NCD-G-60.

[0075] The surface morphology of NCD-G-60 was observed by field emission scanning electron microscopy (FESEM); the phase components of NCD-G-60 were detected by microconfocal laser Raman spectrometer (Raman); the electrochemical related properties of NCD-G-60 were detected by electrochemical workstation; and the element content and functional group composition on the surface of NCD-G-60 were characterized by X-ray photoelectron spectrometer (XPS).

[0076] Fig. 9 , Fig.10The FESEM images of the nano-diamond / graphite composite film electrode NCD-G-60 at 10,000 times and 100,000 times after electrochemical oxidation for 60 minutes at a treatment voltage of +0.5V are shown respectively. Fig. 9 It can be seen that the NCD-G-60 composite thin film electrode is a dense film formed by many large spherical particles connected together, and the underlying silicon substrate is not exposed. Fig.10 It can be observed that there are many angular and irregularly shaped tiny nanoparticles on the surface of these large spherical particles.

[0077] Fig.11 , Fig.12 The nano-diamond / graphite composite film electrode NCD-G-60 was electrochemically oxidized for 60 min at a treatment voltage of +0.5 V at 800-2200 cm -1 and 2200-3500cm -1 Raman spectrum of the band. Fig.11 The Raman spectrum in the image is composed of 1140, 1250, 1332, 1350, 1470, 1580cm -1 The typical Raman spectrum of nanodiamond thin film electrode is composed of six characteristic peaks. -1 and 1470cm -1 The peak at is attributed to the sp 2 CC vibration, 1250cm -1 The peak at 1332 cm is caused by the broadened vibrational density of states of diamond clusters with smaller grain size and tetrahedral amorphous carbon. -1 The peak at 1350cm is a typical diamond characteristic peak. -1 The D peak at the graphite grain boundary is disordered or other structural defects at the sp 2 Bond stretching vibration related, 1580cm -1 The G peak at is caused by the sp 2 The hybrid CC bond vibration is generated. In addition, Fig.12 The Raman spectrum of the -1 There are two characteristic peaks, corresponding to the 2D peak of the double frequency Raman characteristics of the complete dispersion of phonons related to single-layer or few-layer graphene and the D+D' peak related to the expression of auxiliary defects. Fig.11 It can be calculated that the diamond content in NCD-G-60 is 32.30%, I D / I G The value is 1.13, and the half-peak width of the G peak is 97.32 cm -1 .

[0078] Fig.13 , Fig.14The cyclic voltammetry curves of the nano-diamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5 V in 1M KCl and 1M KCl+1mM K3Fe(CN)6 electrolytes at a scan rate of 100mV / s; Fig.13 It can be seen that the potential window of NCD-G-60 is 3.50 V (vs RHE), the hydrogen evolution potential is -1.74 V (vs RHE), and the background current is 2.59 mA / cm 2 .Depend on Fig.14 It can be seen that the electrochemical active area C of NCD-G-60 A 531.2μC / cm 2 Compared with NCD-G in Comparative Example 1, the hydrogen evolution potential of NCD-G-60 in Example 1 shifted negatively by about 0.16 V, and the background current decreased by about 3.78 mA / cm 2 Compared with the glassy carbon electrode and boron-doped diamond film electrode purchased in Comparative Examples 2 and 3, the background current of NCD-G-60 is 67.28 mA / cm lower than that of the commercially purchased glassy carbon electrode and boron-doped diamond film electrode. 2 , 20.38mA / cm 2 . .

[0079] Fig.15 , Fig.16 They are the XPS spectrum corresponding to the broad spectrum and the fitting diagram of the O1s spectrum of the nanodiamond / graphite composite film electrode NCD-G-60 electrochemically oxidized for 60 min at a treatment voltage of +0.5V. Fig.15 Semi-quantitative calculation of the relative contents of C1s and O1s in NCD-G-60 showed that the content of C1s was 87.42At%, and the content of O1s was 9.31At%. Fig.16 As shown, the O 1s energy spectrum is mainly composed of three characteristic peaks with binding energies of 531.3eV, 532.2eV, and 533.1eV. The characteristic peak at 531.3eV is the peak related to the C=O bond, the characteristic peak at 532.2eV is the peak related to the C-OH bond, and the characteristic peak at 533.1eV is the peak related to the COC bond. Fig.16 Semi-quantitative calculation of the relative content of oxygen-containing groups in the O1s spectrum shows that the content of C=O is 3.05At%, the content of C-OH is 3.21At%, and the content of C=O is 3.05At%. Compared with NCD-G in Comparative Example 1, the O1s content of NCD-G-30 in Example 1 increases by about 4.50At%.

[0080] Example 3

[0081] Diamond powder with a particle size of 500nm and deionized water are mixed evenly in a ratio of 1g:100ml, and the mixed solution is then placed in an ultrasonic cleaner for 20 minutes to evenly disperse the diamond powder in the solution to obtain a diamond seeding solution; the diamond seeding solution is taken on a polishing flannel cloth, and a single crystal silicon wafer is ground back and forth at the seeding solution for 20 minutes to grind the seeding crystal, and then the ground seeded single crystal silicon wafer is placed in the diamond seeding solution for 30 minutes of ultrasonic seeding, and then the obtained single crystal silicon wafer is washed with deionized water and blown dry with nitrogen to finally obtain a seeded single crystal silicon wafer.

[0082] The seeded single crystal silicon wafer was placed as a substrate in a hot wire chemical vapor deposition device, tantalum wire was used as the metal wire, acetone was used as the carbon source, and high-purity hydrogen with a flow rate of 80sccm was used to bring the acetone into the reaction chamber, and high-purity hydrogen with a flow rate of 200sccm was introduced, the growth power was controlled to be 2200W, the growth pressure was 1.0kPa, and the growth time was 90min; after the growth was completed, the acetone was stopped, and the voltage was slowly reduced to 0V at a rate of 1V / min in high-purity hydrogen, so that the power was reduced to 0W, and a nanodiamond / graphite composite thin film electrode was obtained, which was named NCD-G.

[0083] The processing voltage of the electrochemical workstation was set to +0.5V, and the nanodiamond / graphite composite film electrode NCD-G was placed in a 0.5M H2SO4 solution and connected to the electrochemical workstation for 90 minutes of electrochemical anodization treatment to obtain a nanodiamond / graphite composite film electrode with high hydrogen evolution potential and low background current, which was named NCD-G-90.

[0084] The surface morphology of NCD-G-90 was observed by field emission scanning electron microscopy (FESEM); the phase components of NCD-G-90 were detected by microconfocal laser Raman spectrometer (Raman); the electrochemical related properties of NCD-G-90 were detected by electrochemical workstation; and the element content and functional group composition on the surface of NCD-G-90 were characterized by X-ray photoelectron spectrometer (XPS).

[0085] Fig.17 , Fig.18 The FESEM images of the nanodiamond / graphite composite film electrode NCD-G-90 at 10,000 times and 100,000 times of electrochemical oxidation for 90 minutes at a treatment voltage of +0.5V are shown respectively. Fig.17 It can be seen from the graph that the NCD-G-60 composite thin film electrode is a dense film formed by connecting many large spherical particles, without exposing the underlying silicon substrate. Fig.18 It can be observed that there are many irregularly shaped tiny nanoparticles on the surface of these large spherical particles.

[0086] Fig.19 , Fig. 20 The nano-diamond / graphite composite film electrode NCD-G-90 was electrochemically oxidized for 90 min at a treatment voltage of +0.5 V at 800-2200 cm -1 and 2200-3500cm -1 Raman spectrum of the band. Fig.19 The Raman spectrum in the image is composed of 1140, 1250, 1332, 1350, 1470, 1580cm -1 The typical Raman spectrum of nanodiamond thin film electrode is composed of six characteristic peaks. -1 and 1470cm -1 The peak at is attributed to the sp 2 CC vibration, 1250cm -1 The peak at 1332 cm is caused by the broadened vibrational density of states of diamond clusters with smaller grain size and tetrahedral amorphous carbon. -1 The peak at 1350cm is a typical diamond characteristic peak. -1 The D peak at the graphite grain boundary is disordered or other structural defects at the sp 2 Bond stretching vibration related, 1580cm -1 The G peak at is caused by the sp 2 The hybrid CC bond vibration is generated. In addition, Fig. 20 The Raman spectrum of the -1 There are two characteristic peaks, corresponding to the 2D peak of the double frequency Raman characteristics of the complete dispersion of phonons related to single-layer or few-layer graphene and the D+D' peak related to the expression of auxiliary defects. Fig.19 It can be calculated that the diamond content in NCD-G-90 is 35.69%. D / I G The value is 1.11, and the half-peak width of the G peak is 95.17 cm -1 .

[0087] Fig.21 , Fig. 22 The cyclic voltammetry curves of the nano-diamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min in 1M KCl and 1M KCl+1mM K3Fe(CN)6 electrolytes at a scan rate of 100mV / s are shown respectively; Fig.21 It can be seen that the potential window of NCD-G-90 is 3.84 V (vs RHE), the hydrogen evolution potential is -2.10 V (vs RHE), and the background current is 0.73 mA / cm 2 .Depend on Fig. 22It can be seen that the electrochemical active area C of NCD-G-90 A 509.6μC / cm 2 Compared with NCD-G in Comparative Example 1, the hydrogen evolution potential of NCD-G-90 in Example 1 increased significantly, shifted negatively by about 0.52 V, and the background current decreased by about 5.64 mA / cm 2 Compared with the glassy carbon electrode and boron-doped diamond film electrode purchased in Comparative Examples 2 and 3, the background current of NCD-G-90 is 69.14 mA / cm lower than that of the commercially purchased glassy carbon electrode and boron-doped diamond film electrode. 2 , 22.24mA / cm 2 .

[0088] Fig.23 , Fig.24 They are the XPS spectrum broad spectrum and the fitting diagram of O1s spectrum of the nanodiamond / graphite composite film electrode NCD-G-90 electrochemically oxidized for 90 min at a treatment voltage of +0.5 V. Fig.23 Semi-quantitative calculation of the relative contents of C 1s and O 1s in NCD-G-90 showed that the content of C1s was 87.02 At%, and the content of O 1s was 10.10 At%. Fig.24 As shown, the O 1s energy spectrum is mainly composed of three characteristic peaks with binding energies of 531.3eV, 532.2eV, and 533.1eV. The characteristic peak at 531.3eV is the peak related to the C=O bond, the characteristic peak at 532.2eV is the peak related to the C-OH bond, and the characteristic peak at 533.1eV is the peak related to the COC bond. Fig.24 Semi-quantitative calculation of the relative content of oxygen-containing groups in the O1s spectrum showed that the content of C=O was 3.23At%, the content of C-OH was 3.57At%, and the content of C=O was 3.30At%. Compared with NCD-G in Comparative Example 1, the O1s content of NCD-G-30 in Example 1 increased by about 5.29At%.

[0089] Comparative Example 1

[0090] Diamond powder with a particle size of 500nm and deionized water are mixed evenly in a ratio of 1g:100ml, and the mixed solution is then placed in an ultrasonic cleaner for 20 minutes to evenly disperse the diamond powder in the solution to obtain a diamond seeding solution; the diamond seeding solution is taken on a polishing flannel cloth, and a single crystal silicon wafer is ground back and forth at the seeding solution for 20 minutes to grind the seeding crystal, and then the ground seeded single crystal silicon wafer is placed in the diamond seeding solution for 30 minutes of ultrasonic seeding, and then the obtained single crystal silicon wafer is washed with deionized water and blown dry with nitrogen to finally obtain a seeded single crystal silicon wafer.

[0091] The seeded single crystal silicon wafer was placed as a substrate in a hot wire chemical vapor deposition device, tantalum wire was used as the metal wire, acetone was used as the carbon source, and high-purity hydrogen with a flow rate of 80sccm was used to bring the acetone into the reaction chamber, and high-purity hydrogen with a flow rate of 200sccm was introduced, the growth power was controlled to be 2200W, the growth pressure was 1.0kPa, and the growth time was 90min; after the growth was completed, the acetone was stopped, and the voltage was slowly reduced to 0V at a rate of 1V / min in high-purity hydrogen, so that the power was reduced to 0W, and a nanodiamond / graphite composite thin film electrode was obtained, which was named NCD-G.

[0092] The surface morphology of NCD-G was observed by field emission scanning electron microscopy (FESEM); the phase components of NCD-G were detected by microconfocal laser Raman spectrometer (Raman); the electrochemical related properties of NCD-G were detected by electrochemical workstation; and the element content and functional group composition on the surface of NCD-G were characterized by X-ray photoelectron spectrometer (XPS).

[0093] Fig.25 , Fig.26 These are FESEM images of nanodiamond / graphite composite film electrode NCD-G at 10,000 times and 100,000 times respectively. Fig.25 It can be seen that the NCD-G composite film electrode is a dense film formed by connecting many large spherical particles. Fig.26 It can be observed that there are many tiny nanoparticles on the surface of these large spherical particles.

[0094] Fig. 27 , Fig.28 The nano-diamond / graphite composite film electrode NCD-G is 800-2200cm -1 and 2200-3500cm -1 Raman spectrum of the band. Fig. 27 The Raman spectrum in the image is composed of 1140, 1250, 1332, 1350, 1470, 1580cm -1 The typical Raman spectrum of nanodiamond thin film electrode is composed of six characteristic peaks. -1 and 1470cm -1 The peak at is attributed to the sp 2 CC vibration, 1250cm -1 The peak at 1332 cm is caused by the broadened vibrational density of states of diamond clusters with smaller grain size and tetrahedral amorphous carbon. -1 The peak at 1350cm is a typical diamond characteristic peak. -1 The D peak at the graphite grain boundary is disordered or other structural defects at the sp 2Bond stretching vibration related, 1580cm -1 The G peak at is caused by the sp 2 The hybrid CC bond vibration is generated. In addition, Fig.28 The Raman spectrum of the -1 There are two characteristic peaks, corresponding to the 2D peak of the double frequency Raman characteristics of the complete dispersion of phonons related to single-layer or few-layer graphene and the D+D' peak related to the expression of auxiliary defects. Fig. 27 It can be calculated that the diamond content in NCD-G is 26.56%, I D / I G The value is 1.07, and the half-peak width of the G peak is 105.88 cm -1 .

[0095] Fig.29 , Fig.30 The cyclic voltammetry curves of nanodiamond / graphite composite film electrode NCD-G in 1M KCl and 1M KCl+1mMK3Fe(CN)6 electrolytes at a scan rate of 100mV / s are shown respectively; Fig.29 It can be seen that the potential window of NCD-G is 3.32V (vs RHE), the hydrogen evolution potential is -1.58V (vs RHE), and the background current is 6.37mA / cm 2 .Depend on Fig.30 It can be seen that the electrochemical active area C of NCD-G A 526.2μC / cm 2 .

[0096] Fig.31 , Fig.32 They are the broad spectrum corresponding to the XPS spectrum of the nanodiamond / graphite composite film electrode NCD-G and the fitting diagram of the O 1s spectrum. Fig.31 Semi-quantitative calculation of the relative contents of C1s and O1s in NCD-G showed that the content of C1s was 94.89At%, and the content of O1s was 4.81At%. Fig.32 As shown, the O 1s energy spectrum is mainly composed of three characteristic peaks with binding energies of 531.3eV, 532.2eV, and 533.1eV. The characteristic peak at 531.3eV is the peak related to the C=O bond, the characteristic peak at 532.2eV is the peak related to the C-OH bond, and the characteristic peak at 533.1eV is the peak related to the COC bond. Fig.32 Semi-quantitative calculation of the relative content of oxygen-containing groups in the O1s energy spectrum shows that the content of C=O is 1.55At%, the content of C-OH is 1.61At%, and the content of C=O is 1.65At%.

[0097] Comparative Example 2

[0098] Fig.33 The cyclic voltammetry curve of the commercial glassy carbon electrode purchased in 1 mol / L KCl solution at a scan rate of 100 mV / s. Fig.33 It can be observed that the background current of the glassy carbon electrode can reach up to 69.87 mA / cm 2 .

[0099] Comparative Example 3

[0100] Fig.34 The cyclic voltammetry curve of the purchased commercial boron-doped diamond film electrode in 1 mol / L KCl solution at a scan rate of 100 mV / s. Fig.34 It can be observed that the background current of commercial boron-doped diamond thin film electrodes can reach up to 22.97 mA / cm 2 .

Claims

1. A method for preparing a nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current, characterized in that: The steps include: (1) Seed crystal pretreatment Ultrasonic dispersion of diamond powder in deionized water to obtain diamond seeding liquid, taking the diamond seeding liquid on a polishing flannel, grinding a single crystal silicon wafer back and forth at the seeding liquid to grind the seeding crystal, then placing the single crystal silicon wafer after the seeding crystal is ground in the diamond seeding liquid for ultrasonic seeding, then taking it out, washing it with deionized water, and drying it with nitrogen to obtain a single crystal silicon wafer after seeding; (2) Hot Wire Chemical Vapor Deposition Using the seeded single crystal silicon wafer obtained in step (1) as a substrate, tantalum wire as a metal wire, and acetone as a carbon source, a nano-diamond / graphite composite thin film electrode is prepared by hot wire chemical vapor deposition; (3) Electrochemical anodizing treatment The nano-diamond / graphite composite film electrode obtained in step (2) is placed in a H2SO4 solution and subjected to electrochemical anodization treatment at a voltage of +0.5V for 30 to 90 minutes to obtain the nano-diamond / graphite composite film electrode with high hydrogen evolution potential and low background current.

2. The method for preparing the nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: In step (1), the particle size of the diamond powder is 500 nm.

3. The method for preparing the nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: In step (1), the mass volume ratio of diamond powder to deionized water is 1:100, g / mL.

4. The method for preparing the nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: In step (1), diamond powder is ultrasonically dispersed in deionized water for 20 minutes.

5. The method for preparing a nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: In step (1), the grinding seeding time is 20 minutes, and the ultrasonic seeding time is 30 minutes.

6. The method for preparing the nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: The operation method of step (2) is as follows: the seeded single crystal silicon wafer is placed as a substrate in a hot wire chemical vapor deposition device, tantalum wire is used as a metal wire, acetone is used as a carbon source, and acetone is brought into the reaction chamber by bubbling high-purity hydrogen with a flow rate of 80 sccm. At the same time, high-purity hydrogen with a flow rate of 200 sccm is introduced, and the growth power is controlled to be 2200 W, the growth pressure is 1.0 kPa, and the growth time is 90 min. After the growth is completed, the acetone is stopped, and the voltage is slowly reduced to 0 V at a rate of 1 V / min in high-purity hydrogen, so that the power is reduced to 0 W, thereby obtaining a nano-diamond / graphite composite thin film electrode.

7. The method for preparing the nano-diamond / graphite composite thin film electrode with high hydrogen evolution potential and low background current as claimed in claim 1, characterized in that: In step (3), the concentration of the H2SO4 solution is 0.5M.

Citation Information

Cited By

  • Preparation method of nano-diamond / graphite composite film electrode with high electrochemical activity

    CN119956391A

  • Preparation method of nanodiamond / graphite composite film electrode with high electrochemical activity

    CN119956391B